Analysis of the use of ecosystem goods and services in a rural community in eastern Guatemala - Vargas-Gálvez, Carlos (2019)
egradation of natural ecosystems and rural landscapes contributes to reducing the natural capital of human communities by increasing their vulnerability, due, for example, to the reduction of food sources or contamination of water bodies. In this study, we characterize the ecosystem goods and services used by a rural community in the municipality of Zacapa and analyze, through network analysis, how these resources are used by a group of families in the community. As a result, the goods most commonly used by the community were water, firewood, the tree locally known as ocote (by-product of Pinus maximinoi), mint, Melipona bee honey (Melipona spp.), orange, rue (Graveolens route L.), the sun, goosefoots (Chenopodium sp.), and Sija sage (Lippia sp.). The network analysis showed low connectivity between community families regarding ecosystem goods and services. In addition, low connectivity was observed between families regarding resource use. No wild animals were reported in the diet of the families interviewed, although mammalian skins and ornaments were observed in some houses.